2022
DOI: 10.3390/vaccines10050763
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Vaccines against SARS-CoV-2 among Polish Patients with Multiple Sclerosis Treated with Disease-Modifying Therapies

Abstract: (1) Background: The present study aims to report the side effects of vaccination against coronavirus disease 2019 (COVID-19) among patients with multiple sclerosis (MS) who were being treated with disease-modifying therapies (DMTs) in Poland. (2) Methods: The study included 2261 patients with MS who were being treated with DMTs, and who were vaccinated against COVID-19 in 16 Polish MS centers. The data collected were demographic information, specific MS characteristics, current DMTs, type of vaccine, side effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In one of our previous works, we collected a database of more than 2000 individuals with MS from Poland, and the relapse rate after vaccination against COVID-19 was low ( 7 ). Similarly, low relapse incidence after vaccination was described by Kong et al ( 8 ), including individuals with neuromyelitis optica spectrum disorder (NMOSD).…”
Section: Discussionmentioning
confidence: 99%
“…In one of our previous works, we collected a database of more than 2000 individuals with MS from Poland, and the relapse rate after vaccination against COVID-19 was low ( 7 ). Similarly, low relapse incidence after vaccination was described by Kong et al ( 8 ), including individuals with neuromyelitis optica spectrum disorder (NMOSD).…”
Section: Discussionmentioning
confidence: 99%
“…There are quite a number of studies on the safety of the COVID-19 vaccine in patients with MS. In a Polish study of 2261 MS patients who received the COVID-19 vaccine, 70.6% (1597/2261) of patients experienced side effects after vaccination, but most of them were mild symptoms such as flu-like symptoms and injection site pain [ 15 ]. In addition, only 4.4% (99/2261) of patients experienced a relapse after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, vaccination is a complex issue in this population considering that these patients are frequently subjected to immunomodulatory or immunosuppressive treatments. A number of recent studies of patients with MS have shown that COVID-19 vaccination does not increase the risk of clinical relapse and serious adverse events, suggesting favorable safety of COVID-19 vaccine in MS patients [14][15][16]. The issue of immunogenicity of COVID-19 vaccines in relation to MS medications has also been evaluated in some studies [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, despite the above rare case reports, it is mostly considered that the benefits of SARS-CoV-2 vaccines vastly outweigh the potential risks [ 116 ]. Most adverse events following vaccination are mild, and the acute relapse incidence is low [ 118 ].…”
Section: Neurological Complications Following Covid-19 Vaccinationmentioning
confidence: 99%